Incidence of loiasis clinical manifestations in a rural area of the Republic of Congo: Results from a longitudinal prospective study (the MorLo project). - Jérémy T Campillo; Biam-Miveck Pakat-Pambou; Bachiratou Sahm; Sébastien D S Pion; Marlhand C Hemilembolo; Elodie Lebredonchel; Michel Boussinesq; François Missamou; Cédric B Chesnais (PLoS Neglected Tropical Diseases)
Background Loiasis is endemic in Central Africa. Despite evidence of clinical complications and increased mortality, it remains excluded from the list of neglected tropical diseases. The main manifestations are Calabar swellings (CS), Eyeworm (EW) and non-specific general symptoms such arthralgia and pruritus. We calculated incidence rates for clinical manifestations of loiasis from a 13-month study on clinical manifestations in 991 individuals living in Loa loa-endemic areas in the Republic of Congo. Methodology From September 2022 to September 2023, community health workers collected weekly symptoms from cohort participants. Detailed data on symptom duration, intensity, associated pruritus, and impact on sleep were recorded. Laboratory procedures included thick blood smear for L. loa microfilaremia measurement, creatininemia measurement and eosinophilia counts. We used multiple failure analysis and frailty models to calculate incidence rates of EW, CS, arthralgia, pruritus and absence from work (AfW) and to analyses factors associated with increased incidence of each symptom. The population-attributable fractions (PAFs) associated with loiasis were also calculated for pruritus, AfW and arthralgia. Principal findings Among the studied manifestations, arthralgia had the highest incidence rate at 555.2 cases per 1000 Person-Year (PY), followed by pruritus (332.3 cases/1000 PY), AfW (298.6/1000 PY), EW (266.4/1000 PY), and CS (213.8/1000 PY). Notably, the incidence rates of CS, pruritus, arthralgia, and AfW were statistically significantly higher in the subgroup of individuals who experienced at least one episode of EW during the follow-up period. EW occurrence is more frequent when microfilaremia is present. The PAFs of AfW, pruritus and arthralgia, associated with loiasis was 18.0% [07.3-27.6], 20.8% [11.6-29.1] and 12.1% [3.1-20.1], respectively. Conclusion/significance This is the first study to provide incidence rates for the clinical manifestations of loiasis. These estimates are crucial for assessing the burden of loiasis. The findings highlight the disease's impact on quality of life.